Gastrointestinal manifestations of mitochondrial disorders: a systematic review. (January 2017) - Finsterer, Josef; Frank, Marlies
Mitochondrial disorders (MIDs) due to respiratory-chain defects or nonrespiratory chain defects are usually multisystem conditions [mitochondrial multiorgan disorder syndrome (MIMODS)] affecting the central nervous system (CNS), peripheral nervous system, eyes, ears, endocrine organs, heart, kidneys, bone marrow, lungs, arteries, and also the intestinal tract. Frequent gastrointestinal (GI) manifestations of MIDs include poor appetite, gastroesophageal sphincter dysfunction, constipation, dysphagia, vomiting, gastroparesis, GI pseudo-obstruction, diarrhea, or pancreatitis and hepatopathy. Rare GI manifestations of MIDs include dry mouth, paradontosis, tracheoesophageal fistula, stenosis of the duodeno-jejunal junction, atresia or imperforate anus, liver cysts, pancreas lipomatosis, pancreatic cysts, congenital stenosis or obstruction of the GI tract, recurrent bowel perforations with intra-abdominal abscesses, postprandial abdominal pain, diverticulosis, or pneumatosis coli. Diagnosing GI involvement in MIDs is not at variance from diagnosing GI disorders due to other causes. Treatment of mitochondrial GI disease includes noninvasive or invasive measures. Therapy is usually symptomatic. Only for myo-neuro-gastro-intestinal encephalopathy is a causal therapy with autologous stem-cell transplantation available. It is concluded that GI manifestations of MIDs are more widespread than so far anticipated and that they must be recognized as early as possible to initiate appropriate diagnostic work-up and avoid any mitochondrion-toxic treatment.